PRAKTIK-PRATIK GREEN HUMAN RESOURCE MANAGEMENT DI ORGANISASI (Studi Kasus pada IKM Tenun Ikat Praikundu) - Osfred Umbu Djadji; Sifra Varah Veronika Lena (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to analyze and determine Green Human Resource Management (GHRM) Practices in the Praikundu Ikat Weaving Small and Medium Industry (IKM), East Sumba district. Data was collected through interviews and observations and analyzed qualitatively. This study concludes that GHRM practices at Praikundu Ikat Weaving have been implemented but are not optimal and there are still several GHRM functions that have not been implemented, such as; Environmentally Friendly Training & Development, Environmentally Friendly Performance Evaluation and Environmentally Friendly Compensation. This function is not implemented optimally because the scale of IKM is still relatively small, production capacity is limited and takes a long time, sales levels are not consistent, human resources capacity is still low, there is no guidance and management of human resources and there is no clear organizational structure. Apart from that, GHRM functions that have been implemented well include Green Recruitment, Green Selection and Green Performance Evaluation. This function is implemented well because IKM is a cultural heritage business that produces ikat products made from natural raw materials and has distinctive characteristics so that the image of IKM is increasingly recognized by the public and has an impact on the 3 functions of GHRM.